AQUEOUS EXTRACT OF FICUS BENGALENSIS BARK DECREASES OXIDATIVE ACTIVITY IN STREPTOZOTOCIN-INDUCED DIABETIC RATS (International Journal of Food and Nutritional Sciences, 2021)
One of the major etiologies in pathogenesis of diabetes especially complications is oxidative stress. In this present investigation the aqueous extracts of Ficus benghalensis bark antioxidant properties had been studied in albino rats with streptozotocin-induced diabetes. Oral administration of Ficus benghalensis bark extracts for 6 weeks result as reduction of Thiobarbituric acid reactive substances (TBARS) and hydroperoxides. Aqueous extract of Ficus benghalensis bark at a dose of 150 mg/kg BW significantly increased in the reduced glutathione (GHS), superoxide dismutase (SOD), catalase (CAT) in liver of streptozotocin (STZ) -induced diabetic rats. These results clearly indicated that the antioxidant effect of aqueous extract and a dose at 500 μg/kg BW of glibenclamide reduced the oxidative stress in diabetic rats. Medicinal plants are not only a mean of health care, but make an important contribution to poverty eradication to livelihoods of poor communities all over the world. World trade in medicinal plants accounts for about 30 percent of the total drug market. Interest in medicinal plants business has been rapidly growing field and has commercial and socio-economic significance.